Heights in enslaved and indentured populations from west-central Africa, 1839-1896 - Matos, P. T. de; Jelmer Vos; Mourits, Rick (Fifth Conference of the European Society of Historical Demography, 2023)
This paper analyzes heights, as a measure of human welfare, in a nineteenth-century west-central African population using anthropometric data of individuals enslaved or indentured in the Novo Redondo region of Angola. From the 1830s, Novo Redondo witnessed increasing levels of enslavement, which on the one hand supplied the export slave and indentured labour trade and, on the other, supported the expansion of plantation agriculture in the region itself. Registers of Liberated Africans shipped from Novo Redondo and Quicombo between 1839 and 1844 and of Africans contracted in Novo Redondo for labour service in São Tomé e Príncipe between 1876 and 1896 provide the name, origin, sex, age, and height of thousands of Africans in this region. By analyzing heights across these two periods, relating heights to origin, sex, and age, we first aim to establish trends in nutrition and health in Novo Redondo’s enslaved population. In addition, we aim to offer a preliminary explanation of these trends by placing them in historical and comparative context.